KOMITMEN PERUSAHAAN DALAM IMPLEMENTASI PROGRAM CSR BEASISWA PENDIDIKAN PT KRAKATAU STEEL YANG BERMITRA DENGAN LP3I CILEGON, BANTEN - Pondalus, Albar Meky; Fawzi, Indra Lestari (UI Scholars Hub, 2021)
The financial crisis in 2017 made many SOEs reduce and even stop the CSR program. PT Krakatau Steel, one of the largest SOEs experiencing financial difficulties remains committed to its CSR program to keep it going. One of PT Krakatau Steel's CSR programs that is still running is an educational scholarship in partnership with LP3I Cilegon. The program, which has been running since 2007, is a form of PT Krakatau Steel's commitment to solving the social problems in Cilegon, namely low education, poverty and unemployment. This research uses a qualitative approach with descriptive type. The purposive of this study is to describe the implementation of company commitment in CSR Educational Scholarships along with its supporting and inhibiting factors. The results showed that there are external factors, interaction factors, and internal factors that supported the company’s commitment in implementing the CSR Scholarship Program. In addition, obstacles were found that could threaten the sustainability of the program, such as: Limited budget, Lack of Commitment by Scholarship recipients, Lack of communication between company and partner, and Scholarship recipients.